Design, synthesis, DFT calculations, molecular docking and antimicrobial activities of novel cobalt, chromium metal complexes of heterocyclic moiety-based 1, 3, 4-oxadiazole derivatives. Issue 22 (12th December 2022) - Rohand, Taoufik; Ben EL Ayouchia, Hicham; Achtak, Hafid; Ghaleb, Adib; Derin, Yavuz; Tutar, Ahmet; Tanemura, Kiyoshi
Abstract: A Schiff base, 5-(4-methylphenyl)-4-[(pyridin-2-ylmethylidene)amino]-4 H -1, 2, 4-oxadiazole as a bidentate ligand has been synthesized by the reaction between the 4-amino-5-(4-methylphenyl)-4 H -1, 3, 4-oxadiazole and aromatic aldehyde. The Schiff base reacted with CoCl3 ·6H2 O and CrCl3 ·6H2 O in ethanol to yield 1, 3, 4-oxadiazole complexes. The structures of synthesized ligand and their complexes have been established on the basis of their IR, Mass and 1 H-NMR spectra. Electronic and geometric structures of both cobalt and chromium complexes were investigated by density functional theory (DFT) and quantum theory of atoms in molecules (QTAIM) calculations. DFT-based reactivity calculations estimated the studied system as strong electrophile and/or strong nucleophile in polar organic reactions. Moreover, most reactive sites were predicted theoretically based on the delocalized and localized indexes. The nature of Ligand-Metal chemical bonding is discussed in terms of the natural bond orbital (NBO) and QTAIM analysis. Accordingly, the metal ions such as cobalt and chromium are bidentate coordinated with the Schiff base by nitrogen atoms of imine function and pyridine, to form stable complexes. Furthermore, the chromium ions have an affinity superior to the cobalt ions towards Schiff base ligand. In addition, the results of the antibacterial activity in-vitro show that the metal complexation confers an increase in the antibacterial activity of the complexed ligand compared to the free ligand against both Gram-positive and Gram-negative bacteria with broad spectrum activity. In silico molecular docking studies of the ligands and their complexes were applied to describe the probable binding modes into the active site of Escherichia coli ( E. coli ) FabH and Salmonella typhimurium LT2 neuraminidase (STNA) receptors. The increase in biological activity could be attributed to the high stability of the complexes and strong affinities to bacterial enzyme receptors. Communicated by Ramaswamy H. Sarma Abstract : UF0001